Revealing the effect of 2D carbides with different metal sites for improving hydrogen storage in MgH2 - Ren, Kaixiang; Wang, Bingbing (Frontiers in Chemistry, 2022)
Two-dimensional (2D) carbon materials are considered as efficient catalysts for improving hydrogen storage in MgH2, but their catalytic mechanisms of different materials remain unclear. Herein we compare the hydrogen storage properties of MgH2 with doping different 2D carbon materials for revealing their catalytic effecting mechanisms. It can be seen that the effect of 2D metal carbides including Nb2C and Ti2C are superior to 2D graphene for improving hydrogen storage properties of MgH2, where the Ti2C exhibits the best catalytic effect. This is related to the changes of individual metal and graphite chemical valence states of catalysts. The high catalytic activity of the hydrogen storage reaction originates from its unique layered structure and in situ formation of MHX, i.e., the tiny metal crystals can serve as a channel to facilitate hydrogen transport in MgH2 matrix. Moreover, the Ti catalytic effect is better than Nb, which originates from the surface of the multivalent Ti atoms is an intermediate of the electron moving between H- and Mg2+, thus leading to the Ti2C catalyzed MgH2 with superior hydrogen kinetic and cyclic performance.